Cross-sectional analysis of insulin resistance in hypothyroid patients at rural teaching hospital: An endocrinal synergy - Janhavi Mahajan; Anuj Varma; Sunil Kumar; Sourya Acharya; Samarth Shukla; Manjeet Kothari; Rinkle Gemnani (Journal of Family Medicine and Primary Care)
Background: A glucose homeostasis condition known as insulin resistance (IR) is characterized by a decreased sensitivity of adipose tissue, muscle fiber, liver, and other bodily tissues to insulin, even in the presence of normal or elevated blood concentrations of the hormone. Nevertheless, it is uncommon to evaluate the comorbidity of insulin resistance and thyroid discrepancies, particularly the order in which these indicators appear. This study emphasizes the association between hypothyroidism and insulin resistance. Material and Method: Eighty individuals with suspected thyroid illness or related problems were recruited for this cross-sectional study at the AVBR Hospital in Wardha between December 2020 and September 2022. The participants were categorized as having subclinical hypothyroidism, overt hypothyroidism, or controls based on the thyroid indicators detected in their serum. The Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) was used to perform the calculations. A Chi-square test was used in addition to control to examine the relationship between insulin resistance and thyroid function. Results are considered statistically significant only if the P value is less than 0.05. Results: Levels of HOMA-IR were lowest in the Controls (1.65), followed by the Subclinical Group (2.03), and highest in the Overt Group (5.00). HOMA-IR had a significant positive relationship with thyroid stimulating hormone, fasting insulin, and fasting blood sugar (FBS). The prevalence of insulin resistance was 64.3% in overt hypothyroid patients and 36% in subclinical hypothyroid patients. In contrast, it was 21% in the control group of hypothyroid patients on thyroxine therapy for over two months. Conclusion: Thyroid levels and the IR were significantly correlated. The prevalence of insulin resistance was 64.3% in overt hypothyroid and 36% in subclinical hypothyroid in this part of rural area. Therefore having awareness at the primary care physician level may prevent its morbid complications even assessed.